A Systematic Literature Review of Psychological Factors Influencin Future Anxiety Among Emerging Adults - Harvi Wahyu Putriadi; Siti Maimunah (International Journal of Psychology and Health Science, 2026)
Future anxiety is an emotional condition characterized by fear, doubt, and worry regarding the possibility of negative events occurring in the future. This condition is commonly experienced by emerging adults, particularly those aged 20–29 years, as they encounter various developmental demands and uncertainties related to education, career, and social roles. Given its substantial impact on mental well-being, identifying the psychological factors that influence future anxiety is essential. This study aims to identify, classify, and synthesize the psychological factors associated with future anxiety among emerging adults. The study employed a Systematic Literature Review (SLR) method following the PRISMA guidelines. Literature searches were conducted through reputable international databases, namely ScienceDirect, MDPI, Frontiers, and Springer, with inclusion criteria limited to original research articles published between 2021 and 2026. A total of 20 articles were analyzed using thematic mapping techniques. The findings indicate that future anxiety is influenced by both cognitive-dispositional factors and macro-environmental factors. Risk factors include intolerance of uncertainty, pessimism, depressive symptoms, career-related stress, social isolation, low sense of belonging, helicopter parenting, and concerns regarding global crises. In contrast, protective factors include resilience, self-efficacy, and adaptive emotion regulation. These findings highlight the importance of strengthening internal psychological resources through interventions focused on emotion regulation, enhancement of self-efficacy, and support for career transition processes.